Parental childhood maltreatment exposure and deviations in normative cortical and subcortical brain volumes in 5-year-olds - Aho, Sofia (My University, 2026)
Background Parental childhood maltreatment exposure (CME) has been associated with alterations in offspring brain development from infancy to adolescence, as well as an increased risk of developing behavioural or psychopathological issues later in life. The present study examined the associations between maternal and paternal childhood maltreatment and structural brain volumes in 5-year-old children, including cortical and subcortical brain volumes. Additionally, sex-specific associations are investigated. Methods The study included 166 participants from the FinnBrain Birth Cohort Study. Data included structural MRI images and brain volume centiles (gray matter volume, subcortical gray matter volume, and white matter volume) of children at age five. Parental CME was assessed using The Trauma and Distress Scale (TADS) questionnaire, and maternal prenatal and postnatal distress were measured using self-report questionnaires, the Edinburgh Postnatal Depression Scale (EPDS) and the Symptom Checklist-90 (SCL-90). Standardized global brain volumes were used to investigate whether CME is associated with the brain’s state of development in offspring compared to people of same age and sex. Data processing and statistical analyses were conducted using SPSS and RStudio, with multiple linear regression models applied. Results No significant associations were observed between parental childhood maltreatment exposure, measured with TADS scores, and offspring brain volumes in children at the age of 5. Girls exhibited higher gray matter volume compared to boys. Higher maternal age at term, as well as higher maternal education levels were positively associated with gray matter volume. In sex-stratified models, higher maternal age at term was positively associated with gray matter volume in girls and higher maternal education levels were positively associated with gray matter volume in boys.
Keywords: adverse childhood experiences; brain imaging; brain development; childhood maltreatment; childhood trauma; gray matter; subcortical gray matter; white matter